Generation of one iPSC line (IMEDEAi007-A) by Sendai Virus transduction of PBMCs from a Psoriasis donor - Sara Vallejo-Diez; Aarne Fleischer; José María Martín-Fernández; Almudena Sánchez-Gilabert; Carmelo Gómez-Martínez; Mónica Castresana; Daniel Bachiller (Stem Cell Research, 2020)
Psoriasis is a chronic inflammatory skin disease that speeds up the life cycle of skin cells, forming scales and red patches that are itchy and sometimes painful. It is a complex disease of autoimmune origin and genetic predisposition with more than 10 different loci associated. Here we described the production of an iPSC line generated by Sendai Virus (Klf4, Oct3/4, Sox2 and c-Myc) reprogramming of Peripheral Blood Mononuclear Cells (PBMCs) from a Psoriasis patient. The iPSC line generated has normal 46XY karyotype, is free of SeV genome and transgenes insertions, express high levels of pluripotency markers and can differentiate into all three germ layers.